Care work - Marugán Pintos, Begoña (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The origin of the term "care work" is in the debates on the "domestic work" of socialist feminists of the seventies. From these discussions, since mid eighties, feminism has shown how domestic and care work that women are doing allows men to carry out their activities in the public sphere, to children have values and standards, training and physical and emotional development and to communities have some social cohesion. Despite the importance of domestic work, the social norm of employment in the postwar social contract granted citizenship rights only to persons employed, so that domestic and care work, as not being paid, don't granted this rights. Therefore, in addition to clarify the term, this text aims to assess care work as a source of rights assignment. If "we are challenged to build a new culture of transnational law, able to meet the remaining systemic crises" (Fariñas, 2010:120) voices like care and care work enables us to build foundations of the current unequal rights and deconstruct the narrative of the crisis, by creating new proposals more just and egalitarian for the entire population.
Keywords: Care; care work; feminism; inequality; rights